Influence of Ad libitum or Control Feeding on the Performance of Broilers Fed Diets Low in Crude Protein - Waldroup, P.W.; Jiang, Q.; Fritts, C.A. (International Journal of Poultry Science, 2005)
Reduction of dietary crude protein (CP) with amino acid supplementation has been effective in reducing the cost of poultry feed. However, the performance of broilers declines when CP levels reaches a point and can not be totally restored with amino acid supplementation. This study was conducted to determine if differences in feed intake were responsible for the reduced performance at low protein levels. Diets were formulated to meet 100% of NRC (1994) recommendations for indispensable amino acids (Lys at 110%) with CP levels of 16%, 18%, 20%, 22% or 24% with the CP and metabolic energy (ME) equivalency values of amino acids considered in the diet formulation. A minimum dietary electrolyte balance of 200 meq/kg was maintained. There were two feeding regimes including ad libitum feeding and control feeding with a total of ten treatments. All birds were provided a complete 24% CP diet ad libitum from one to 7 d. At 7 d chicks were weighed and placed on test diets containing the various levels of CP. One group remained on ad libitum feeding while the other group was control fed. Feeding diets with less than 20% CP resulted in the loss of BW and impaired feed conversion ratio (FCR) regardless of feeding regimes. There was no significant difference in feed intake and mortality among different dietary treatments in both feeding regimes. Reduction in feed intake does not appear to be the cause of reduced performance on diets low in CP.